Impact of property speculation & cooling measures on private residential property prices & the future of shoebox units in singapore. - Teo, Kok Ho. (2013)
This report studies the impact of property speculation and the recent property cooling measures on private residential property prices in Singapore. In addition, we also discuss the development of shoebox units and their future demand.